HUBUNGAN PERSEPSI MUTU PELAYANAN DENGAN KEPUASAN PELANGGAN - LUBIS, KARTIKA SARI (Komunitas Manajemen Kompetitif, 2018)
This study aims to determine the impact of service quality on customer satisfaction in UPT. The Environmental Health office and Laboratory Riau Province. Respondents in this study were patient in Laboratory of Dinas Kesehatan Provinsi Riau of 96 people. Based on the results of hypothesis testing using simple linear regression analysis method and processed by using SPSS program version 16.0, the results obtained that In the coefficient of determination (R²), obtained value R = 0.585 this means the influence of independent variables (Service Quality) to the dependent variable (Customer Satisfaction) is 58.5%. While the remaining 41.5% is influenced by other variables that are not included in this regression model.Keywords: Service Quality, Customer Satisfaction